PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVd SD NEGERI 59 BONCAH MAHANG - Susi Lestari; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was carried out because of low learning outcomes Mathematics fourth grade students of SD Negeri 59 Boncah Mahang. Of the 32 students who achieve KKM many as 17 people (53.12%) while students who did not complete (46.87%) with an average of 59.06. the purpose of this research is to improve learning outcomes Mathematical IVD grade students of SD Negeri 59 Boncah Mahang denganp Problem Based Learning model. The results of this study showed the average value of 59.06 Basic Scores increased in the first cycle of 3.70% to 61.25. the second cycle of the average value of students also increased by 26.35% to 74.62% on a base score completeness result of learning mathematics students only 53.12% (Action Completed) after application of the model teacher PBM in the first cycle classical completeness obtained are increased to increase to 74.62% , Activity Cycle I teacher at the first meeting of 74.37% with both categories. The second meeting increased to 80% in both categories. At the first meeting of the second cycle at 85% with the category very well, at the second meeting increased to 90% with very good category. Activities of students in the first cycle of the first meeting obtain sufficient percentage of 60% category. The second meeting 75% with very good category. In the second cycle at the first meeting of student activity increased to 80% with very good category. And at the second meeting increased to 85% with very good category. Key Words: Problem Based Learning, Mathematics learning outcome